2020
DOI: 10.1002/jat.4060
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of nicotine salt‐containing e‐liquids

Abstract: “Pod‐based” e‐cigarettes such as JUUL are currently the most prevalent electronic nicotine delivery systems (ENDS) in the United States. JUUL‐type ENDS utilize nicotine salts protonated with benzoic acid rather than freebase nicotine. However, limited information is available on the cellular effects of these products. Cytoplasmic Ca2+ is a universal second messenger that controls many cellular functions including cell growth and cell death. Of note, dysregulation of cell Ca2+ homeostasis has been linked with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Our previous work (Ghosh et al, 2020;Zhang et al, 2020) as well as the work of others (Rowell et al, 2020) have implicated the potential role of increased intracellular Ca 2+ as the mechanism of e-liquid-induced cytotoxicity in vitro (Figure 1A). In particular, it has been questioned if e-liquids may activate endoplasmic reticulum (ER)-resident Ca 2+ release as the mechanism of toxicity (Ghosh et al, 2020). To further examine this premise, we utilized our model and the well-described inositol triphosphate FIGURE 3 | 2-APB treatment reverses some of the effects of MHV infection in mouse lungs.…”
Section: Modeling a Sars-like Infection In Vaping Primed Lungsmentioning
confidence: 79%
“…Our previous work (Ghosh et al, 2020;Zhang et al, 2020) as well as the work of others (Rowell et al, 2020) have implicated the potential role of increased intracellular Ca 2+ as the mechanism of e-liquid-induced cytotoxicity in vitro (Figure 1A). In particular, it has been questioned if e-liquids may activate endoplasmic reticulum (ER)-resident Ca 2+ release as the mechanism of toxicity (Ghosh et al, 2020). To further examine this premise, we utilized our model and the well-described inositol triphosphate FIGURE 3 | 2-APB treatment reverses some of the effects of MHV infection in mouse lungs.…”
Section: Modeling a Sars-like Infection In Vaping Primed Lungsmentioning
confidence: 79%
“…Based upon our previous in vitro studies investigating the role of Ca 2+ in e-liquid-induced cytotoxicity and inflammation [ 12 , 14 ] and our observations of enhanced acute lung pathology after vaped e-liquid pre-exposure and K . pneumoniae infection in comparison to the vaped vehicle followed by K .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a previous assessment of JUUL e-liquids has illustrated notable signs of cytotoxicity in cultured airway epithelial cells [ 12 ]. Studies have also tied together an observable cytotoxicity after e-liquid exposure with increases in cytoplasmic calcium (Ca 2+ ) [ 12 14 ]. These earlier studies led us to further investigate the cellular effects of e-liquids in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature has presented a convincing association between the use of either the traditional combustible cigarette or e-cigarette use/vaping, and Ca 2+ signaling and its dysregulation, which ultimately results in the cytotoxicity of pulmonary epithelia. In brief, we (and others) have utilized both in vitro and in vivo models to demonstrate that exposure to e-cigarette liquids (e-liquids, which are the actual products consumed during the vaping process) can elevate cytosolic Ca 2+ levels and result in significant cytotoxicity and/or pathology [3,[5][6][7][8]. Indeed, while one study has demonstrated that Ca 2+ influx is diminished within the bronchial epithelia of traditional smokers, which is due to decreased ORAI3-dependent Ca 2+ mobilization [3], studies have also shown that certain e-liquid flavor combinations specifically increase cytosolic Ca 2+ levels within both the human bronchial epithelial cell line CALU-3 and primary-derived human bronchial epithelial cells.…”
mentioning
confidence: 99%
“…We have further utilized pharmacology, that is, small molecule treatments, to strengthen the association between a dual exposure, i.e., bacterial or viral challenge with prior vaping exposure, and Ca 2+ -mediated pathology. Finally, vaping has been theorized to induce the polarization of M0 macrophages to pro-inflammatory M1 macrophages, which is a process documented to be mediated by increased intracellular Ca 2+ levels [7,9]. Thus, vaping may trigger macrophage polarization and lead to the accumulation of populations of inflammatory macrophages within the lung, which would increase pulmonary inflammation.…”
mentioning
confidence: 99%